Digital Payment: A Hybrid Sistematic Literature Review And Bibliometric Analysis - Muhammad Tody Arsyianto; Sudarmiatin Sudarmiatin; Agus Hermawan (Global Management: International Journal of Management Science and Entrepreneurship, 2025)
Research on digital payment systems has grown rapidly over the past decades; however, comprehensive and in‑depth studies that synthesize existing empirical findings remain limited. This study aims to conduct a systematic literature review and bibliometric analysis on digital payment research based on empirical publications indexed in Scopus. Using the keyword “Digital Payment” in the article title, abstract, and keywords, a total of 485 documents published between 1989 and 2025 were identified. The evaluation was conducted on November 30, 2025, and the collected data were analyzed using bibliometric techniques with VOSviewer software. The findings reveal a significant surge in digital payment research beginning in 2016, with its peak occurring during 2023–2025, in line with the accelerating digital economic transformation worldwide. Knowledge production has shifted toward emerging economies—particularly India, Indonesia, and Malaysia—supported by dense inter‑institutional and inter‑author collaboration networks. Research themes have expanded beyond technical payment system aspects to interdisciplinary issues involving technology, finance, financial inclusion, human behavior, public policy, and the application of machine learning for security and system optimization. Journal sources, affiliations, authors, and keyword analyses confirm that digital payments have become essential infrastructure for the modern economy and a rich empirical domain for advanced studies on financial stability, consumer protection, regulation, and digital financial innovation.